Adaptasi dan Inovasi: Fragmentasi Sosial dalam Transisi Kepemimpinan Pesantren - Masrur Luai Sadullah (CV. Laskar Karya, 2025)
Leadership transitions in Islamic boarding schools (pesantren) often present complex social dynamics due to social fragmentation involving various actors with differing interests. This study aims to analyze the impact of social fragmentation on leadership transition at Pondok Pesantren Nurul Jadid, particularly in the Jalaluddin Ar-Rumi region, and to explore adaptive and innovative strategies used to maintain institutional stability. Employing a qualitative approach with a case study design, the research involves caretakers, administrators, alumni, and senior students as participants. Data collection techniques include in-depth interviews, participatory observation, and document analysis, while data analysis follows the Miles and Huberman interactive model with source and method triangulation. The findings reveal that social fragmentation manifests in structural, cultural, and relational dimensions, leading to both active and passive resistance toward the new leadership. Adaptive strategies are applied using Parsons’ AGIL framework, including structural compromise, institutional identity reformulation, social integration by religious leaders, and the preservation of traditional values. The novelty of this research lies in the integration of the AGIL theory with the socio-cultural dynamics of islamic boarding schools intersection that has been rarely explored. This study provides both theoretical implications for Islamic educational organizational studies and practical insights for islamic boarding schools in managing leadership transitions constructively. With adaptive and innovative approaches, leadership transitions can be directed as opportunities to strengthen institutional integrity, rather than becoming a source of internal polarization.